Understanding and Mitigating Academic Burnout and Learned Helplessness Among Vocational College Students in China - Yong, Cao; Seok, Chua Bee (Journal of Posthumanism, 2025)
Academic burnout and learned helplessness are significant psychological challenges faced by vocational college students in China, with detrimental effects on their academic performance and mental health. This study explores the interplay between these two phenomena, examining their causes and consequences within the unique context of China’s vocational education system. Drawing on theoretical frameworks such as Maslach’s burnout model and Seligman’s learned helplessness theory, the research highlights how systemic issues—including high academic workloads, societal stigma, and inadequate support systems—contribute to emotional exhaustion, disengagement, and diminished self-efficacy among students. A comprehensive literature review reveals a bidirectional relationship between burnout and helplessness, creating a vicious cycle that exacerbates psychological distress. The study identifies gaps in current research, such as the lack of integrated models and context-specific interventions. To address these challenges, the paper proposes actionable recommendations for educators, institutions, families, and policymakers, emphasizing student-centered pedagogy, mental health support, and societal recognition of vocational education. By adopting a multidimensional approach, stakeholders can mitigate these issues and foster a more inclusive and supportive environment for vocational students, ultimately enhancing their well-being and academic success.